Heimwerken als Protest. Instandbesetzer und Wohnungsbaupolitik in West-Berlin während der 1980er-Jahre - Reinhild Kreis (Zeithistorische Forschungen, 2017)
In the early 1980s, hundreds of men and women in many West German and West European cities resorted to a rather unusual form of protest. In order to express their dissatisfaction with the local housing situation and policies, they occupied empty apartment buildings and, under the eyes of an astonished public, began renovating them themselves. Focusing on West Berlin as the most prominent case, this article interprets the performance of DIY home improvement tasks in occupied buildings (Instandbesetzer, as they called themselves) as a form of protest, thus drawing attention to the manual work done by squatters and its impact on the housing policies of the 1980s. The DIY measures undertaken publicly by the squatters drew attention to serious political and social shortcomings while at the same time demonstrating possible solutions. The visible (or at least announced) transformation of the built environment forced politicians, the public, and experts alike to discuss both housing policy in general and the idea of self-help as suggested by the squatters. Squatters thus accelerated the readjustment of a housing policy which now incorporated manual self-help by tenants into West Berlin’s city planning, but by the same token also undermined the potential for protest and provocation of such practices.